Huma Betang Cultural Influence in Moderating Budgetary Participation in Budgetary Slack - ., Gayatri; Octaviani, Theresia (Udayana Journal of Social Sciences and Humanities; Vol 2 No 2 (2018): UJoSSH, September 2018DO - 10.24843/UJoSSH.2018.v02.i02.p10, 2018)
The purpose of this research is to find out the influence of budgetary participation and huma betang cultural moderation on budgetary slack. The population consists of 28 Palangkaraya’s Regional Apparatus Working Units, Central Kalimantan Province. Proportionate random sampling is used as the sample selection technique. Furthermore, data collection technique is conducted through the questionnaires distribution to 100 respondents. As for the data analysis techniques, simple linear regression analysis is used to test the first hypothesis, and moderation regression analysis with the absolute difference test is employed to test the second hypothesis. The results show that budgetary participation has a positive effect on budgetary slack and the culture of huma betang moderates the relationship of budgetary participation toward budgetary slack. Hence, the suggestion for the next research is that it should be performed in all local government budgeting process.